1999
DOI: 10.1074/jbc.274.3.1226
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Is Required for the Peroxidase Function of Cu,Zn-Superoxide Dismutase at Physiological pH

Abstract: Cu,Zn-superoxide dismutase (SOD1) acts as a peroxidase in the presence of H 2 O 2 at high pH (pH > 9). The high pH species of H 2 O 2 , HO 2 ؊ , was previously implicated as the reactive species. However, recent EPR studies of the enzyme performed in the physiological pH range 7.4 -7.6 with the spin trap 5,5-dimethyl-1-pyrolline-Noxide attributed the intense EPR signal of 5,5-dimethyl-1-pyrolline-N-oxide-OH obtained from SOD1 and H 2 O 2 to the peroxidase activity of the enzyme. The present study establishes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
75
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 50 publications
8
75
3
2
Order By: Relevance
“…The investigators concluded that the bicarbonate anion, anchored to arginine 141 at the active site of SOD1, facilitated the redox cleavage of H 2 O 2 that led to enhanced peroxidase activity (1). In the present study, this interpretation is challenged, and an alternate mechanism for HCO 3 Ϫ -mediated increase in SOD1 peroxidase activity is provided.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…The investigators concluded that the bicarbonate anion, anchored to arginine 141 at the active site of SOD1, facilitated the redox cleavage of H 2 O 2 that led to enhanced peroxidase activity (1). In the present study, this interpretation is challenged, and an alternate mechanism for HCO 3 Ϫ -mediated increase in SOD1 peroxidase activity is provided.…”
mentioning
confidence: 57%
“…Recently, it was reported that the bicarbonate anion (HCO 3 Ϫ ) 1 is required for peroxidase activity and the peroxidase function of copper-zinc superoxide dismutase (SOD1) (1). The peroxidase activity of SOD1 was determined using the electron spin resonance (ESR) technique to monitor the oxidation of spin trap 5,5Ј-dimethyl-1-pyrroline-N-oxide (DMPO) to the DMPO-hydroxyl radical adduct (DMPO-OH).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While considering carbonic anhydrases, it is reasonable to ask whether this ubiquitous family of enzymes might play a defensive role by catalyzing the hydration of CO 2 , which can be oxidized to CO 3 •Ϫ , in contrast to HCO 3 Ϫ , which cannot. In support of this supposition is the report by Götz et al (10) (4) and that HCO 3 Ϫ specifically binds in the solvent access channel of SOD1 and, while so bound, becomes oxidized, at which time the resulting CO 3 •Ϫ protrudes sufficiently to oxidize substrates in the bulk solution (6). Reaction conditions shown are essentially as in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Any valid mechanism must explain the dual requirement for HCO 3 Ϫ and CO 2 and also the involvement of O 2 Ϫ . Moreover, analogy with the Cu,ZnSOD ϩ H 2 O 2 system indicates that CO 3 •Ϫ is a likely participant, whereas HO • is not (1,(3)(4)(5)(6)(7)(8) Ϫ , yet rapid H 2 O 2 consumption is a hallmark of this process.…”
mentioning
confidence: 99%